Hooked [large type] : how crafting saved my life - Foster, Sutton (Grand Central Publishing Large Print, 2021)
The Broadway and television actress discusses how cross-stitching, crocheting, painting and other craft projects kept her sane while dealing with an agoraphobic mother, a painful public divorce, and struggles with fertility.